The reality of the practice of principals of public schools in Jeddah Governorate for interactive theory of leadership and its relationship to the level of administrative creativity they have from their own point of view in light of the Corona pandemic - Alzahrani, Sharefa Ali; Alsaigh, Najat Mohammad (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the reality of the practice of principals of public schools in Jeddah Governorate for the interactive theory of leadership and its relationship to their level of administrative creativity from their own point of view in light of the Corona pandemic. A descriptive correlational approach was adopted, whereby an electronic questionnaire was employed as a tool. The research population consists of principals of public schools in the city of Jeddah, where a random sample of (150) males and females was chosen. The results of the study revealed that the reality of public school principals’ practice of the interactive theory of leadership as a whole came with a high degree, with an arithmetic mean of (3.87). The practice of administrative creativity, with its dimensions, came to a high degree, with an arithmetic mean of (3.77). Moreover, the study showed that there is a significant and positive correlation between the application of interactive theory and administrative creativity in all its dimensions in educational institutions in Jeddah in light of the Corona pandemic. The study recommends the need to develop communication skills that support creativity for leaders and heads of departments in educational institutions.